UPAYA PENINGKATAN PARTISIPASI DAN KEAKTIFAN PESERTA DIDIK DALAM PROSES PEMBELAJARAN DENGAN PEMANFAATAN CANVA DI UPT SPF SD CENTRE MANGALLI - Rahmi, Nur; Herman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study explores efforts to increase student participation and engagement in the learning process at UPT SPF SD Centre Mangalli using Canva as a teaching tool. Low student involvement is a significant challenge faced by educators. By integrating Canva, a user-friendly digital platform, into classroom activities, this study aims to foster creativity and enhance student engagement. A qualitative descriptive method was employed, involving observation, interviews, and documentation. The findings show that Canva significantly improved students' active participation and interest in learning, making the learning experience more interactive and engaging.